Induced Pluripotent Stem Cell Model of Pulmonary Arterial Hypertension Reveals Novel Gene Expression and Patient Specificity - Sa, Silin; Gu, Mingxia; Chappell, James; Shao, Ning-Yi; Ameen, Mohamed; Elliott, Kathryn A. T.; Li, Dan; Grubert, Fabian; Li, Caiyun G.; Taylor, Shalina; Cao, Aiqin; Ma, Yu; et al. (American journal of respiratory and critical care medicine, 2017)
Idiopathic or heritable pulmonary arterial hypertension is characterized by loss and obliteration of lung vasculature. Endothelial cell dysfunction is pivotal to the pathophysiology, but different causal mechanisms may reflect a need for patient-tailored therapies. Endothelial cells differentiated from induced pluripotent stem cells were compared with pulmonary arterial endothelial cells from the same patients with idiopathic or heritable pulmonary arterial hypertension, to determine whether they shared functional abnormalities and altered gene expression patterns that differed from those in unused donor cells. We then investigated whether endothelial cells differentiated from pluripotent cells could serve as surrogates to test emerging therapies. Functional changes assessed included adhesion, migration, tube formation, and propensity to apoptosis. Expression of bone morphogenetic protein receptor type 2 (BMPR2) and its target, collagen IV, signaling of the phosphorylated form of the mothers against decapentaplegic proteins (pSMAD1/5), and transcriptomic profiles were also analyzed. Native pulmonary arterial and induced pluripotent stem cell-derived endothelial cells from patients with idiopathic and heritable pulmonary arterial hypertension compared with control subjects showed a similar reduction in adhesion, migration, survival, and tube formation, and decreased BMPR2 and downstream signaling and collagen IV expression. Transcriptomic profiling revealed high kisspeptin 1 (KISS1) related to reduced migration and low carboxylesterase 1 (CES1), to impaired survival in patient cells. A beneficial angiogenic response to potential therapies, FK506 and Elafin, was related to reduced slit guidance ligand 3 (SLIT3), an antimigratory factor. Despite the site of disease in the lung, our study indicates that induced pluripotent stem cell-derived endothelial cells are useful surrogates to uncover novel features related to disease mechanisms and to better match patients to therapies.